A strategy to maximize astaxanthin production from Haematococcus pluvialis in a cost-effective process by utilizing a PBR-LGP-PBR array (PLPA) hybrid system using light guide panel (LGP) and solar cells. (May 2023) - Lee, Ju Yeon; Yu, Byung Sun; Chang, Won Seok; Sim, Sang Jun
Graphical abstract: Highlights: LGP was placed between each PBR in the PLPA hybrid system. The arrangement of dense PBRs prevented cell growth inhibition. The ROI was increased by 6.55 times at the 10-ton scale. The ROI was increased by 4.71 times at the 100-ton scale. Payout time was reduced by 1.37 times than conventional system at the 100-ton scale. Abstract: This study evaluated economic feasibility through production efficiency, return on investment (ROI) and payout time of a hybrid system using a photobioreactor (PBR)-light guide panel (LGP)-PBR array (PLPA) and solar cells developed for astaxanthin and ω-3 FA simultaneous production of Haematococcus pluvialis . The economic feasibility of the PLPA hybrid system (8 PBRs) and the PBR-PBR-PBR array (PPPA) system (8 PBRs) was evaluated for producing high-value products while effectively reducing CO2 . Introducing a PLPA hybrid system has increased the amount of culture per area by 1.6 times. Also, the shading effect was effectively suppressed with an LGP placed between each PBR, increasing biomass and astaxanthin productivity by 3.39-fold and 4.79-fold, respectively compared to the untreated H. pluvialis cultures. In addition, ROI increased by 6.55 and 4.71 times, and the payout time was reduced by 1.34 and 1.37 times, respectively in 10 and 100-ton scale processes.